In silico analysis revealed hsa-miR-19a-3p and hsa-miR-19b-3p as two potential inhibitors of EGF mRNA in Breast Cancer - Nuha, Nabiha Tahsin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2024.